2023
DOI: 10.3390/ijms24076446
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Drugs as Emerging Immune Modulators in Cancer

Abstract: Despite recent advances in treatment approaches, cancer is still one of the leading causes of death worldwide. Restoration of tumor immune surveillance represents a valid strategy to overcome the acquired resistance and cytotoxicity of conventional therapies in oncology and immunotherapeutic drugs, such as immune checkpoint inhibitors and immunogenic cell death inducers, and has substantially progressed the treatment of several malignancies and improved the clinical management of advanced disease. Unfortunatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The anticancer efficacy of niclosamide has been demonstrated in several cancers, both in vitro using cultured cells and in vivo using mouse xenografts [ 24 , 25 , 26 ]. The results of the present study offer further supportive evidence for the potential of niclosamide as an anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer efficacy of niclosamide has been demonstrated in several cancers, both in vitro using cultured cells and in vivo using mouse xenografts [ 24 , 25 , 26 ]. The results of the present study offer further supportive evidence for the potential of niclosamide as an anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have identified niclosamide, an FDA-approved antiparasitic drug, as a potent inhibitor of the function and expression of SLC38A5 and SLC7A11, consequently inducing oxidative stress, lipid peroxidation and ferroptotic cell death in TNBC cells and suppressing the growth of a TNBC cell line into tumors in mouse xenografts. Niclosamide is known to elicit anticancer effects via multiple mechanisms in several cancer types [ 24 , 25 , 26 ]. The findings of the present study provide yet another novel, hitherto unknown, pharmacological mechanism for the anticancer efficacy of this drug.…”
Section: Introductionmentioning
confidence: 99%
“…Levamisole hydrochloride [LMS, (6 S )-6-phenyl-2,3,5,6-tetrahydroimidazo­[2,1- b ]­[1,3]­thiazole hydrochloride] (Figure ) is an anthelminthic drug, which is widely used for the treatment of parasitic, viral, and bacterial infections . Recent studies have shown that levamisole hydrochloride is effective in the treatment of Krohn’s disease, rheumatoid arthritis, and diseases, such as hepatitis, colon cancer, and refractory genital warts. LMS was reported to have only one solid form in the CSD (KOSPUD). However, no cocrystals of LMS were reported in prior articles.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond characterizing the molecular profile of cancer patients, the efficacy of immunotherapy can also be improved once combined with selected anthelmintic drugs [12], which have already shown important antineoplastic effects [13]. In this regard, the halogenated salicylanilide compound niclosamide was found to affect Signal Transducer and Activator of Transcription 3 (STAT3) phosphorylation and related PD-L1 expression in oncogene-addicted advanced-stage NSCLC patients, while flubendazole, which belongs to the benzimidazole family, exerted similar effects on STAT3, affecting PD-1 expression.…”
mentioning
confidence: 99%
“…In this regard, the halogenated salicylanilide compound niclosamide was found to affect Signal Transducer and Activator of Transcription 3 (STAT3) phosphorylation and related PD-L1 expression in oncogene-addicted advanced-stage NSCLC patients, while flubendazole, which belongs to the benzimidazole family, exerted similar effects on STAT3, affecting PD-1 expression. Another benzimidazole compound, albendazole, was able to target ubiquilin-4, a protein that interacts with and stabilizes PD-L1, thus promoting its proteasomal degradation [12]. Some anthelmintic agents (rafoxanide and ivermectin) also recently revealed their ability to cause some tumors types to be "immunogenic" via the promotion of a particular form of apoptosis called immunogenic cell death, which allows cancer cells to be recognized and targeted by the immune system [12].…”
mentioning
confidence: 99%